2013
DOI: 10.1002/pmic.201200529
|View full text |Cite
|
Sign up to set email alerts
|

Gender dimorphism in regulation of plasma proteins in streptozotocin-induced diabetic rats

Abstract: In the present study, we examined differentially regulated plasma proteins between healthy control and streptozotocin (STZ)-induced male and female diabetic rats by 2DE-based proteomic analysis. Animal experiments revealed that significantly lower plasma insulin levels were observed in female diabetic rats, consequently resulting in higher blood glucose levels in female diabetic rats. Importantly, plasma levels of sex hormones were significantly altered in a gender-dependent manner before and after STZ treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Data represent mean ± SEM, n = 5 in each group. a p \ 0.05 as compared to the aFC group with the data of Choi et al [23] who did not observe gender-specific differences in controls. This difference may be ascribed to strain-specific variations, as in our study, Wistar rats were used and in the study of Choi et al [23] Sprague-Dawley rats were investigated.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Data represent mean ± SEM, n = 5 in each group. a p \ 0.05 as compared to the aFC group with the data of Choi et al [23] who did not observe gender-specific differences in controls. This difference may be ascribed to strain-specific variations, as in our study, Wistar rats were used and in the study of Choi et al [23] Sprague-Dawley rats were investigated.…”
Section: Discussionmentioning
confidence: 65%
“…a p \ 0.05 as compared to the aFC group with the data of Choi et al [23] who did not observe gender-specific differences in controls. This difference may be ascribed to strain-specific variations, as in our study, Wistar rats were used and in the study of Choi et al [23] Sprague-Dawley rats were investigated. However, the higher content of glucose in control male Wistar rats, as a model, seems to be from this point of view nearer to human population as shown by slightly higher glucose level in men as compared to women without any history of diabetes [24].…”
Section: Discussionmentioning
confidence: 65%
“…In our earlier study, we found that plasma levels of both Ft-A and Ft-B are significantly lower in males after HFD feeding while remarkably higher in females [27]. Moreover, Ft-B has been shown to be up-regulated in plasma of both male and female diabetic rats [28]. Those results led us to hypothesize that gender-dimorphic regulation of fetuins is associated with hormonal effects.…”
Section: Introductionmentioning
confidence: 98%
“…Rat is one of the most commonly used experimental animal and has been utilized as a model organism in almost every biomedical research for human diseases. Many of these studies involved the analysis of plasma proteins since as blood constantly circulate through the body and perfuse the tissues and organs, the protein changes would directly reflect the physiological and pathological status of the animal . The complexity of plasma proteins, however, sets out analytical challenges and generally requires high‐resolution separation and sensitive detection.…”
Section: Introductionmentioning
confidence: 99%
“…In shotgun methods, proteins were directly digested with proteases and the peptide mixtures were analyzed by one‐ or multi‐dimensional LC‐MS/MS . In 2DE‐based methods, proteins were separated on a two‐dimensional gel by the difference of apparent p I and mass, and the protein spots of interest were excised and analyzed as intact proteins or as peptides after in‐gel digestion, using MALDI‐MS or LC‐ESI‐MS . Reference searching revealed that though shotgun proteomics has gained increased popularity, so far 2DE‐MS has still been the main approach for rat plasma proteomic analysis, probably due to the powerful separation of 2DE for proteins in complex mixtures and the capacity to provide straightforward and visible information on the distributions of the intact proteins or polypeptides.…”
Section: Introductionmentioning
confidence: 99%